A test of the mediating effects of social interaction, physical fitness, and alleviation of negative emotions in the influence of physical exercise on residents' subjective wellbeing—empirical analysis based on CGSS 2023 - Zhao, Shutong; Huang, Haiyan (Frontiers in Psychology, 2025)
IntroductionParticipation in physical exercise (PE) can effectively enhance residents' subjective wellbeing; however, additional research is warranted to elucidate the mechanisms by which exercise participation influences population wellbeing. This study aims to investigate the impact of physical exercise on residents' subjective wellbeing and explore its mediating mechanisms, offering deeper insights into the psychological effects of exercise. Additionally, it provides valuable guidance for enhancing public welfare and promoting social harmony.MethodsThis cross-sectional, observational study analyzed the nationally representative 2023 China General Social Survey (CGSS). In line with the CGSS 2023 sampling frame, “residents” were defined as adults aged ≥18 years living in private households across mainland China in both urban and rural areas. After sample screening, we retained 5,377 valid observations. To examine the relationship between physical exercise and subjective wellbeing and its underlying mechanisms, we employed multiple linear regression, ordered probit models, propensity score matching (PSM), stepwise regression, and the Karlson–Holm–Breen (KHB) decomposition.ResultsThe findings indicated that physical exercise was positively associated with Chinese adults' subjective wellbeing. The strength of this association differed across subgroups: individuals with a high school education or less, low income, men, and middle-aged adults showed larger positive associations with subjective wellbeing. Furthermore, the overall association was partially accounted for by differences in social interaction, physical fitness, and negative emotions; these factors operated jointly in relation to subjective wellbeing.ConclusionsThis study identified a positive association between physical exercise and Chinese adults' subjective wellbeing, with social interaction, physical health, and the alleviation of negative emotions functioning as mediating mechanisms in this association. Accordingly, it is recommended that governments, schools, and all sectors of society expand and diversify physical activity (PA) programs and cultivate supportive environments that promote regular exercise, thereby improving population health and wellbeing.